STRATEGI PENGEMBANGAN PETERNAKAN SAPI POTONG BERBASIS AGRIBISNIS DENGAN POLA KEMITRAAN DI KOTA PEKANBARU - Siti; Bintal Amin; Suwondo Suwondo (EcoNews, 2021)
This study aims to formulate a management strategy for the development of agribusiness cattle with partnership pattern in Pekanbaru city. The research was conducted from February to March 2021. The research was conducted using a qualitative approach through survey methods and direct observation in the field. Primary data collection was carried out through observation, in-depth interviews with a structured questionnaire instrument, and data collection of river water environments in Rumbai and Tenayan Raya districts for BOD, COD, Total Koliform tests. Secondary data were obtained from related agencies in this study. The analysis used in this research is descriptive analysis method and SWOT analysis to determine the appropriate management strategy. The results of testing the BOD river water in Rumbai district are below the quality standard, then Tenayan Raya district is above the quality standard, which is 11 mg/L, COD in Rumbai district is still below the quality standard in Tenayan Raya district above the quality standard, which is 36 mg/L, total coliform in Rumbai district is above the quality standard, namely 24,000 jlh/100 ml in Tenayan Raya district below the quality standard. Then, for the results of the development of cattle farm SWOT Analysis, in a strong internal position and responds to existing opportunities to avoid threats. The strategy used by SO is Increasing productivity by utilizing available resources, expanding beef cattle development, Improving the quality of human resources for breeders.